Uranium-bearing francolites present in organic-rich limestones of NW Greece: a preliminary study using synchrotron radiation and fission track techniques - Tzifas, I. T.; Glasmacher, U. A.; Misaelides, P.; Godelitsas, A.; Gamaletsos, P. N.; Goettlicher, J.; Francoso de Godoy, D. [UNESP] (Springer, 2017)
Synchrotron radiation techniques (mu-XRF and mu-XANES) were applied to the study of organic-rich phosphatized limestones of NW Greece (Epirus). The results revealed uranium accumulation in areas of the material containing, among others, carbonate apatite (francolite) and organic matter. The UL (3)-edge of mu-XANES spectra showed that uranium was present in tetravalent form. U-bearing francolite crystals were separated from the rock and characterized by Raman spectroscopy and microprobe. The analysis of the crystals also indicated the presence of sodium and sulfur. The uranium presence in the crystals was also visualized, after neutron irradiation and etching, by the observation of the fission tracks.
Keywords: Uranium; Francolite; Phosphatized limestones; Raman; mu-XRF; mu-XANES; Fission tracks